2021
DOI: 10.1016/j.jbc.2021.100815
|View full text |Cite
|
Sign up to set email alerts
|

Inducible hepatic expression of CREBH mitigates diet-induced obesity, insulin resistance, and hepatic steatosis in mice

Abstract: Edited by Qi-Qun Tang Cyclic AMP-responsive element-binding protein H (CREBH encoded by Creb3l3) is a transcription factor that regulates the expression of genes that control lipid and glucose metabolism as well as inflammation. CREBH is upregulated in the liver under conditions of overnutrition, and mice globally lacking the gene (CREBH −/− ) are highly susceptible to diet-induced obesity, insulin resistance, and hepatic steatosis. The net protective effects of CREBH have been attributed in large part to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…The MS-275-treated mouse livers showed increased mRNA levels of FAO-related genes, but decreased mRNA levels of lipogenic genes ( Figure 6 B,C). In addition, several studies have reported that FGF21 overexpression influences weight loss and hepatic steatosis [ 23 , 24 ]. Therefore, we investigated the expression of Fgf21 in the livers of the MS-275-treated mice.…”
Section: Resultsmentioning
confidence: 99%
“…The MS-275-treated mouse livers showed increased mRNA levels of FAO-related genes, but decreased mRNA levels of lipogenic genes ( Figure 6 B,C). In addition, several studies have reported that FGF21 overexpression influences weight loss and hepatic steatosis [ 23 , 24 ]. Therefore, we investigated the expression of Fgf21 in the livers of the MS-275-treated mice.…”
Section: Resultsmentioning
confidence: 99%